FAKTOR RESIKO AKTIVITAS, MOBILITAS, DAN MENGGANTUNG PAKAIAN TERHADAP KEJADIAN DEMAM BERDARAH PADA ANAK - Istiqomah, Meivin; Syahrul, Fariani (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: DHF is a disease that is caused by dengue virus that transmitted by mosquitos of Aedes genus, especially Aedes aegypti. DHF cases in Indonesia are more dominant in adults of age ≥ 15 years old, however DHF cases in Putat Jaya Surabaya are dominant in children of age <15 years old. This research was conducted to analyze the risk factors for DHF in children of age <15 years old. Methods: The type of this research is analytic observational with case control study. The population of the research consisted of case population that was children of age <15 years old who got DHF illness and the control population was children of age <15 years old who did not get DHF illness. Total sample of the research used a ratio of 1: 1 that was 29 case samples and 29 control samples. The way to take samples used simple random sampling method. The independent variables included activities, mobilities, and the habit of hanging clothes. Data analysis were using simple logistic regression. Results:  The risk factor of DHF in children of age <15 years old was activities. The value of OR in high activity around 3.643 (95% CI = 1.109 < OR <11.969) and OR on moderate activity around 8.500 (95% CI = 1.403 <OR <51.483 Conclusion: The conclusion of this research was only activities that was risk factor for DHF in children of age <15 years old.